Pemanfaatan Limbah Organik Rumah Tangga sebagai Sumber Energi Alternatif - Zaharuddin Zaharuddin; Uun Novalia Harahap; Abdul Azis Syarif; Yetti Meuthia Hasibuan; Deny Walady Utama (Prioritas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Biogas is an innovative product that is able to increase added value in household organic waste. Biogas is the result of the fermentation process of organic waste using Biodigester products. This service aims to help partners utilize organic waste into alternative fuels in the form of biogas. From several experiments that have been carried out, the composition of the comparison of raw materials for organic waste is 5 kg, 5 liters of water, and EM 4 500 ml. The biogas obtained is 13 psi with a long duration of use for 21.33 minutes. Biogas from household organic waste has the advantage of reducing the accumulation of organic waste and utilizing household organic waste as an alternative energy source. Energy from biogas can be used as household fuel. With the presence of biogas from organic waste, Sei Suka Deras Village has an alternative solution in utilizing household organic waste which has been a problem of air pollution, beauty and environmental comfort. Keywords: household organic waste, biodigester, biogas